2010
DOI: 10.1186/1743-422x-7-157
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at positions 186 and 194 in the HA gene of the 2009 H1N1 pandemic influenza virus improve replication in cell culture and eggs

Abstract: Obtaining suitable seed viruses for influenza vaccines poses a challenge for public health authorities and manufacturers. We used reverse genetics to generate vaccine seed-compatible viruses from the 2009 pandemic swine-origin influenza virus. Comparison of viruses recovered with variations in residues 186 and 194 (based on the H3 numbering system) of the viral hemagglutinin showed that these viruses differed with respect to their ability to grow in eggs and cultured cells. Thus, we have demonstrated that mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
(24 reference statements)
2
17
0
Order By: Relevance
“…Indeed, a previous study has found serine in this position to be a human H1N1 characteristic, whereas proline in this position characterizes swine strains (20). Moreover, this position has been recently reported to affect growth in cell culture and eggs (21). Thus, the appearance of serine in pH1N1 may be one of the characteristics leading it to become a more "human-like" virus.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a previous study has found serine in this position to be a human H1N1 characteristic, whereas proline in this position characterizes swine strains (20). Moreover, this position has been recently reported to affect growth in cell culture and eggs (21). Thus, the appearance of serine in pH1N1 may be one of the characteristics leading it to become a more "human-like" virus.…”
Section: Resultsmentioning
confidence: 99%
“…1A), although HA was indeed present and recognized by an anti-pH1N1 MAb (data not shown). The original isolate of the pH1N1 virus does not replicate well in MDCK cells but can be made to propagate well in vitro if critical mutations are incorporated into the receptor-binding pocket of HA (13,27,28). An example is the pH1N1/E3 virus generated in our laboratory by selection of a high-growth clone of pH1N1 in 10-day-old embryonated chicken eggs (13).…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing of our CA/E3/09 virus revealed three mutations in HA (K136N, S200P, and D239G). Due to differences in the numbering system chosen, the S200P mutation corresponds to the S186P mutation in the plasmid F8 genetic mutant CA/09 virus created by Suphaphiphat et al, which has been shown to increase the growth of the virus in either eggs or MDCK cells (36). The single mutation of S to P at position 186 does not change the antigenicity of the virus (36).…”
Section: Discussionmentioning
confidence: 99%
“…Due to differences in the numbering system chosen, the S200P mutation corresponds to the S186P mutation in the plasmid F8 genetic mutant CA/09 virus created by Suphaphiphat et al, which has been shown to increase the growth of the virus in either eggs or MDCK cells (36). The single mutation of S to P at position 186 does not change the antigenicity of the virus (36). In addition, the K136N mutation in our stock virus is in the same position as the K119N mutation found in an MDCK cell-adapted CA/ 07/09 virus (11).…”
Section: Discussionmentioning
confidence: 99%